Russian Borrowings in the Russian Germans Dialects and the Ways of their Translation into Literary German - Олег Дмитриевич Пермяков (Philology & Human, 2018)
The article focuses on the different ways of rendering Russian borrowed words, frequent in the dialects of Russian Germans, while translating them into literary German. For the material of his investigation the author chooses to turn to schwanks – satirical short stories, the genre used to be highly popular in German culture and spread now among the Russian Germans. Translation and the further comparative analysis of the source texts (ST) and target texts (TT) showed that for all the various ways of borrowings translation transliteration combined with the explanations introduced into the text by the translator was the most adequate way to fulfill the task. This method both preserves the cultural specificity of the ST and bridges the lexical and cultural gaps (lacunas) in the process of communication.